Clinical and Phenotypic Characteristics of Early-Onset Inflammatory Bowel Disease: A Five-Year Observational Study - Ivan S. Samolygo; Marina A. Manina; Ekaterina A. Yablokova; Pavel A. Stribul; Alexander V. Novikov; Anton S. Antishin; Albina S. Pestova; Alexander S. Tertychnyy; Daniel Munblit; Svetlana I. Erdes (Children, 2025)
Background: Inflammatory bowel diseases with an early-onset form (EO-IBDs) make up a special disease group with certain clinical and phenotypic characteristics. This article discusses the features of such early onset in a group of children, based on five years of monitoring a registry of children with IBD from a specialized center. Methods: This retrospective single-center cohort study included pediatric patients diagnosed with EO-IBD between 2019 and 2024. Clinical, laboratory, and endoscopic data were collected from medical records, including fecal calprotectin, inflammatory markers, disease activity indices, and endoscopic severity scores. Localization was classified according to the Paris system, and histological activity was assessed using the IBD-DCA score. Results: There were 20 patients with ulcerative colitis (UC) and 17 with Crohn’s disease (CD). Clinical activity was moderate or high (p = 0.179). UC was more characterized by diarrhea and rectal bleeding. CD was more often accompanied by abdominal pain, weight loss, and fever. In total, 82.4% of patients with CD had an inflammatory form. UC-like intestinal lesion was typical of both nosologies—L3 64.7% and E4 60% forms in CD and UC, respectively. Morphological activity was moderate for both nosologies (p = 0.54). IBD-U was present in 43.2% of patients. The median time after which it was possible to diagnose UC was 24 weeks (IQR 20–48) and 40 weeks (IQR 30–45.5) for CD (p = 0.56). Conclusions: Our study confirms the presence of characteristic signs of EO-IBD development, such as a frequent family history of IBD, high or moderate clinical activity during diagnosis verification, colon damage, and a high frequency of extraintestinal manifestations.